(3eaJGM GdMceIs - (3HdZRGf GdJejejs
(3ChdgG (B:s
(3GdMeO ddg GdChd GdPi dG Chd bHdg hGdBNQ GdPi dG BNQ HYOg gPG cJGH CPcQ ajg Ef TGA Gddg JYGdi SQ JQcjH GdCLQGe GdYdhjI hGdSadjI hJCda GdWHGFY s
(3BNQgG (B:s
(3hcPdc GdMjhGf ef HGWf GdXGgQ Ef TGA Gddg JYGdi hEP bO JeefG Gdbhd aejG TQMfGg ef Gdbhd s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
(3JHUQI GdJQGLe(Bs
(3JQLeI GdeDda (B:s
(3JdejP HdjfGS GdMcje s
Keywords: (3GdadSaI hGdefWbs